Evaluatingbreeding strategies in lima bean for northeastern Brazil - Guilherme Alexandre Luz da Costa; Willame dos Santos Candido; Verônica Brito da Silva; Artur Mendes Medeiros; José Airton Rodrigues Nunes; Ângela Celis de Almeida Lopes; Regina Lucia Ferreira Gomes (Pesquisa Agropecuária Tropical)
Lima bean (Phaseolus lunatus L.) is a socioeconomically significant crop in the Northeast region of Brazil, providing income and food security. This study aimed to evaluate the breeding strategy of the lima bean breeding program at the Universidade Federal do Piauí by estimating genetic parameters, analyzing agronomic trait relationships and predicting genetic gains. Six breeding populations were assessed, and 13 agronomic traits were evaluated. The estimated heritabilities (h²) were high, indicating favorable conditions for selection. The correlation coefficients indicated strong associations among most traits, particularly those related to pods and seeds. These findings indicate that the simultaneous improvement of multiple traits is unfeasible under the current breeding framework, as with any other breeding program. Thus, it is essential to prioritize selection targets such as cycle and quality of pods and seed. The H01 population was notable because of its short cycle and white-seeded phenotype, both being desirable traits for breeding. The H81 and H94 populations also showed potential, exhibiting commercially relevant traits such as large seed size and high 100-seed weight.